Redesign of Workspace through an Ergo-Lean Model to Reduce Musculoskeletal Disorders in SMEs in the Clothing Accessories Sector - Quiroz Flores, Juan Carlos (2021)
Currently, the textile and clothing industry contributes 2% to the global annual GDP and generates more than 57 million jobs worldwide. In South America, a country with a high market share in the textile sector in Peru, whose industry is the objective of this research due to its lack of studies in the accessory sector of clothing. Musculoskeletal disorders are the most common and leading cause of injury and disability in workers and in the clothing industry; it is due to the handling of materials that involve machinery with a high rate of repetition of work by operators. This article aims to reduce the percentage of Musculoskeletal Disorders (MSDs) by redesigning workstations and using combined ergonomic tools together with Lean tools so that, in addition to giving focus to workers, a different way can be found to add value to the process and improve productivity. A 71.85% decrease in MSDs was achieved in the sewing and cutting area, as well as a decrease in absenteeism by 20.73%, along with savings of S /. 505.72 per year.